The Mitotic and Metabolic Effects of Phosphatidic Acid in the Primary Muscle Cells of Turbot (Scophthalmus maximus) - Wang, Tingting; Wang, Xuan; Zhou, Huihui; Jiang, Haowen; Mai, Kangsen; He, Gen (Frontiers in Endocrinology, 2018)
Searching for nutraceuticals and understanding the underlying mechanism that promote fish growth is at high demand for aquaculture industry. In the present study, the modulatory effects of soy phosphatidic acids (PA) on cell proliferation, nutrient sensing, and metabolic pathways were systematically examined in primary muscle cells of turbot (Scophthalmus maximus). PA was found to stimulate cell proliferation and promote G1/S phase transition through activation of target of rapamycin (TOR) signaling pathway. The expression of myogenic regulatory factors, including myoD and follistatin was up regulated, while that of myogenin and myostatin was down regulated by PA. Furthermore, PA increased intracellular free amino acid levels and enhanced protein synthesis, lipogenesis and glycolysis, while suppressed amino acid degradation and lipolysis. PA also was found to increased cellular energy production through stimulated tricarboxylic acid (TCA) cycle and oxidative phosphorylation. Our results identified PA as a potential nutraceutical that stimulates muscle cell proliferation and anabolism in fish.